What Do We Know About Sharing Power in Co‐Production in Mental Health Research? A Systematic Review and Thematic Synthesis - India Hopkins; Max Verlander; Lucy Clarkson; Pamela Jacobsen (Wiley, 2024)
ABSTRACT Background Guidance on co‐production between researchers and people with lived experience was published in 2018 by the National Institute for Health and Care Research (NIHR) advisory group, previously known as INVOLVE. This guidance described sharing power as a key principle within co‐production. Authentic sharing of power within co‐produced mental health research does not always occur however and remains a challenge to achieve within many projects. Objectives To explore what has been learned about the sharing of power in co‐production within mental health research since the publication of these guidelines, by synthesising qualitative literature relating to power within co‐produced mental health research. Methods We carried out a systematic review with thematic synthesis. We searched CINHAL, Embase and PubMed databases to identify qualitative or mixed‐method studies relating to power within co‐produced mental health research. Studies were independently screened by two reviewers for inclusion and appraised using the Critical Appraisal Skills Programme tool (CASP) for qualitative research. Results We identified nine papers that met the criteria for inclusion and were included in the synthesis. Three themes were generated: (1) Battling to share power against a more powerful system, (2) Empowerment through relationships and (3) The journey is turbulent, but it is not supposed to be smooth. Conclusions Results highlight that power is pervasive, especially within the hierarchical systems research is often conducted within. Sharing power within co‐produced mental health research is an ongoing complex process that is not intended to be easy. Respectful trusting relationships can help facilitate power sharing. However, ultimately meaningful change needs to come from research funders, universities and NHS providers. Patient or Public Contribution The study authors include a lived experience researcher who contributed to the review design, analysis and write‐up.